Muscle Contractile Characteristics During Exhaustive Dynamic Exercise and Recovery - Rannou, Fabrice; Nybo, Lars; Andersen, Janni Enghave; Nordsborg, Nikolai B. (Frontiers in Physiology, 2021)
Our aim was to provide in vivo assessment of human muscle twitch characteristics during and following exhaustive dynamic exercise to explore temporal alterations of rate of force development (RFD) and relaxation (RFR). Eleven healthy participants (mean age±SD: 24±3 yrs) completed dynamic knee-extensor exercise in randomized order at three different intensities eliciting exhaustion after ~9 min (56±10 W), ~6 min (60±10 W) and ~4 min (63±10 W) in addition to a low intensity (28±5 W) bout. In a novel setup, electrical doublet stimulation of m. vastus lateralis was applied during exercise (every 30 s) and recovery, for frequent evaluation of key contractile properties (maximal force, RFD, RFR and electromechanical delay) in addition to M-wave characteristics. RFD and RFR remained stable throughout the low intensity trial, but declined in all exhaustive trials to reach a similar level of ~40% of pre-exercise values at task failure but with the exponential decay augmented by intensity. Following exhaustion, there was a fast initial recovery of RFD and RFR to ~ 80% of pre-exercise values within 1 min followed by a longer suppression at this level. M-wave characteristics remained unchanged during all trials. In conclusion, this is the first study to quantify intensity-dependent alterations of RFD and RFR during and after exhaustive dynamic exercise in humans. A hypothesized reduction and fast reversion of RFD was confirmed and a surprising compromised RFR is reported. The present unique experimental approach allows for novel insight to exercise induced alterations in human muscle contractile properties which is relevant in health and disease.